Neonatal segmental enteritis due to cow's milk allergy - Pavai Arunachalam; John Mathai (Wolters Kluwer Medknow Publications, 2013)
Cow's milk protein allergy (CMPA) typically presents with persistent diarrhea or dysentery, vomiting and bleeding per rectum in young infants. CMPA is reported to mimic Hirschsprung's disease and malrotation. We report, a neonate who presented with recurrent attacks of segmental enteritis due to CMPA and the last episode presented with signs of peritonitis. He improved dramatically after elimination of cow's milk from his diet. CMPA should be considered in artificially fed babies with surgical abdomen and atypical clinical signs and symptoms.